Perbedaan Pengaruh Metode Latihan Circuit dan Berbeban terhadap Hasil Tembakan Free Throw Pemain Putra Klub Bola Basket Triple V Karanganyar - Muchhamad Sholeh; Bagus Aditya Nugroho; Satrio Sakti Rumpoko; Sunjoyo Sunjoyo; Bagus Kuncoro (Departement of Mathematics Education, 2023)
The objectives of this study are: (1) to determine the difference in the impact of circuit and load training methods on the results of free throw shots of male athletes of the triple V Karanganyar basketball club. (2) Know the practice method that is more effective against the results of basketball free throw shots. This research uses experimental methods in quantitative research. The subjects of the study consisted of 30 athletes of the triple V basketball club of Karanganyar Regency. This research was conducted in Gor Punokawan, Karanganyar Regency. To obtain the necessary data, a basketball shot test was used (Battery test from AAHPERD Basket Ball Test Manual from Johnson & Nelson, 1986: 275-279). The sampling technique used is total sampling. The samples were divided into two groups, namely group 1 consisting of 15 athletes given circuit training treatment, and group 2 consisting of 15 athletes given weighted training treatment. The data collection technique was carried out with a basketball free throw test. Data analysis techniques are carried out by statistical analysis using t tests at the level of significance of 5%. To meet the assumptions of the research results, normality tests, homogeneous tests, difference tests, and percentage increases were carried out. Based on the results of data analysis, the following conclusions were obtained: (1) there is a difference in impact between circuit training methods and weighted training, shown from the calculation results of the final test of each group 1, namely t_hitung = 2.735 and group 2 t_hitung = 2.628 which is greater than t_tabel = 2.145 with a signification level of 5%. (2) both training methods, namely Circuit and weighted, were shown to increase free throw results, with an increase of 16.22% < group 2 of 17.46%